Serial proton magnetic resonance spectroscopy in a patient with the interval form of carbon monoxide poisoning. Issue 1 (January 1995) - Murata, T; Itoh, S; Koshino, Y; Omori, M; Murata, I; Sakamoto, K; Isaki, K; Kimura, H; Ishii, Y
Abstract : Serial proton magnetic resonance spectroscopy (1H-MRS) studies were performed from immediately after the appearance of sequelae in a patient with the interval form of carbon monoxide (CO) poisoning. The volume of interest was set over the frontal lobe white matter. In the early period a persistent increase in choline was found, which was thought to reflect the course of progressive demyelination. The appearance of lactate and decrease in N-acetylaspartate reflected the point at which neuron injury became irreversible. These were followed later by the finding of irreversible changes on MRI and single photon emission computed tomography. The findings suggest that 1H-MRS may be a useful modality to determine neuron viability and prognosis early in the course of the interval form of CO poisoning.